Epileptic “Paroxysmal Arousal” in the Differential Diagnosis of NREM Parasomnia “Confusional Arousal” - Gülçin Benbir Şenel; Rümeysa Unkun; Özge Uygun; S. Naz Yeni; Derya Karadeniz (Archives of Epilepsy, 2023)

(untitled)
Sleep-related hypermotor epilepsy (SHE) should be differentiated from NREM parasomnias in terms of a similar clinical presentation. The lack of ictal and/or interictal epileptic encephalographic (EEG) features in SHE complicates the differential diagnosis. Moreover, epileptic paroxysmal arousal (PA) does not present with associated hyperkinetic motor events typical of SHE, and this should be carefully evaluated from confusional arousal (CA), a type of NREM parasomnia. In this term, this paper aims to present three patients referred to the Sleep and Disorders Unit with the prediagnosis of CA but diagnosed as epileptic PA following video-polysomnography (PSG) with multichannel EEG recordings; and aims to discuss the clinical, EEG, and PSG characteristics of these patients on the basis of literature data.